LITERASI INFORMASI MAHASISWA CALON GURU ANAK USIA DINI TAHUN KEEMPAT DI UNIVERSITAS ISLAM NEGERI RADEN MAS SAID SURAKARTA - Rahmasiwi, Amining (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The explosion of information in the information and digital era requires every human being to have mastery of information literacy to select and use the information correctly and wisely. This study aims to determine the information literacy of prospective early childhood teacher students in the fourth year. The research design used a longitudinal survey with a sample size of 90 students from different academic years. The analysis results were carried out descriptively to determine the average value of student information literacy to be further categorized according to the level of information literacy. The results showed that the average information literacy score of PIAUD students in the fourth year was still not optimal, which was still in the range of 49 to 62 out of 100. Regarding the achievement of indicators, students had good abilities in evaluating information and sources critically and combining data.